Psilocybin-Induced Mystical-Type Experiences are Related to Persisting Positive Effects: A Quantitative and Qualitative Report - McCulloch, Drummond E-Wen; Grzywacz, Maria Zofia; Madsen, Martin Korsbak; Jensen, Peter Steen; Ozenne, Brice; Armand, Sophia; Knudsen, Gitte Moos; Fisher, Patrick MacDonald; Stenbæk, Dea Siggaard (Frontiers in pharmacology, 2022)
Psychedelic drugs such as psilocybin have shown substantial promise for the treatment of several psychiatric conditions including mood and addictive disorders. They also have the remarkable property of producing persisting positive psychological changes in healthy volunteers for at least several months. In this study (NCT03289949), 35 medium-high doses of psilocybin were administered to 28 healthy volunteers (12 females). By the end of the dosing day, participants reported the intensity of their acute experience using the 30-item Mystical Experience Questionnaire (MEQ) and an open-form qualitative report from home. Persisting psychological effects attributed to the psilocybin experience were measured using the Persisting Effects Questionnaire (PEQ) 3-months after administration. Using a linear latent-variable model we show that the MEQ total score is positively associated with the later emergence of positive PEQ effects ( p = 3 × 10 −5 ). Moreover, the MEQ subscales “Positive Mood” ( p corr = 4.1 × 10 −4 ) and “Mysticality” ( p corr = 2.0 × 10 −4 ) are associated with positive PEQ whereas the subscales “Transcendence of Time and Space” ( p corr = 0.38) and “Ineffability” ( p corr = 0.45) are not. Using natural language pre-processing, we provide the first qualitative descriptions of the “Complete Mystical Experience” induced by orally administered psilocybin in healthy volunteers, revealing themes such as a sense of connection with the Universe, familial love, and the experience of profound beauty. Combining qualitative and quantitative methods, this paper expands understanding of the acute psilocybin induced experience in healthy volunteers and suggests an importance of the type of experience in predicting lasting positive effects.